Characterization of Alpelisib in Rat Plasma by a Newly Developed UPLC-MS/MS Method: Application to a Drug-Drug Interaction Study - Wang, Qiong; Lan, Xia; Zhao, Zhuofei; Su, Xiaohang; Zhang, Yuji; Zhou, Xiao-Yang; Xu, Ren-Ai (Frontiers in Pharmacology, 2021)
Alpelisib, an oral selective and small-molecule phosphoinositide 3-kinase (PI3K) inhibitor, was lately approved in the USA to treat breast cancer. We established and validated a sensitive method to quantify alpelisib levels in rat plasma based on ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) technique, which was successfully employed to explore the effects of CYP3A4 inhibitors on alpelisib pharmacokinetics in rats. A C18 column named Acquity UPLC BEH C18 was applied to achieve the separation of alpelisib and internal standard (IS) duvelisib after protein precipitation with acetonitrile. The mobile phase in this study had two components including acetonitrile and water having 0.1 % formic acid, and a program with gradient elution method was used at a 0.40 mL/min flow rate. We operated mass spectrometry in a positive multiple reaction monitoring (MRM) mode. In the scope of 1-5000 ng/mL, this assay had excellent linearity. Our newly developed assay was verified in all aspects of bioanalytical method validation, involving lower limit of quantification (LLOQ), selectivity, accuracy and precision, calibration curve, extraction recovery, matrix effect, and stability. Then we used this assay to detect the plasma levels of alpelisib from a drug-drug interaction investigation. Ketoconazole remarkably increased the plasma concentration of alpelisib and changed alpelisib pharmacokinetics more than itraconazole. This study will help better understand the pharmacokinetic properties of alpelisib, and further clinical studies should be done to confirm this result in patients.